“Zalp” Magazine as a Tool to Support and Form Defense Literature - Anastasia V. Sysoeva (Studia Litterarum, 2022)
The Soviet journal “Zalp” and its supervising organizations, which draw the writers to the military topics, were closely engaged in their activities. Defense literary criticism had the journal as its basis. The journal gave its authors a symbolic capital — introduced them to the community of defense writers, which was especially significant for novices. The work with the latter was a main focus of the journal editorial policy. It also provided an opportunity to publish for professional writers. Discussions, including the one with the participation of a poputchik, as well as ideologically controversial short stories demonstrate that the defense literature of the beginning of 1930s was not entirely restricted. At the same time, there was an idea of the “right” defense text and the journal was a platform for searching for it. This article deals with the cases when the text was recognized as erroneous and the variety of authors’ correction in response to criticism. The fictional texts in the journal were a selection of defense literature’ principles which writers could follow in their work.